Educação de Jovens e Adultos: reflexões sobre a modalidade na formação inicial de professores de matemática da UEFS - Mamona, Sara Soares Costa (2017)
This study aimed to investigate the professional knowledge required by the licensed teacher, in the context of the initial training of mathematics teachers for their work in the Education of Young and Adults - EJA, as a modality of Basic Education. To do so, some of the specific objectives defined were: to identify the professional knowledge oriented to the EJA present in the Pedagogical Proposal of the Course of Mathematics from the State University of Feira de Santana - UEFS, Teaching Menus and Plans; Identify the necessary knowledge to be built during the initial training for a graduate in mathematics to work in the EJA; Contribute to the understanding and reflection about the necessary knowledge for the initial formation of mathematics teachers to work in the EJA. Even though the modality represents an important demand to be attended in the Teaching Network, there are still many professionals who work in the modality without training in the area. Considering that the exit profile of the graduates should meet the demands of Basic Education and how the EJA constitutes it, it is necessary to return the look to the initial formation of teachers. Mathematics was chosen because it is one of the areas considered as the most difficult by the students. A qualitative approach was chosen, with the perspective of constructing a sensitive understanding of the studied phenomenon from the perceptions brought by the research subjects - undergraduates and teacher-trainers with some experience in the EJA. The used techniques were document analysis, semi-structured interviews and questionnaires. The locus of the research was the Course of Mathematics from UEFS. This work is structured in five topics, including an introduction; the second topic brings a survey of the researches on the same object of this work and considerations referring to the chosen methodological path; the third topic refers to the theoretical framework with two chapters that deal with initial teacher training, mathematical questions for teaching in the EJA and the specificities of the EJA, listed in three different dimensions that are related to the EJA individuals, the pedagogical and political-administrative dimensions. The fourth topic brings the discussions of the results from the analysis of course documents, the speeches of the research subjects and the reflections established with the theoretical framework. Finally, final considerations demonstrate that the teaching and the subjects of the EJA, their realities and specificities, are the relevant sources to be understood during the initial formation of mathematics teachers to act in EJA.